Hubungan Lama Penggunaan Ventilator Mekanik dengan Kejadian Ventilator Associated Pneumonia (VAP) pada Pasien Ruang ICU RSUD Karawang” - Kusnanto, Kusnanto; Hafez, Faringga Ismail Al (Universitas Malahayati, 2025)
ABSTRACT Mechanical ventilators are invasive therapies in the form of assistive devices that take over respiratory functions, invasive breaths. Besides being used as a breathing aid, the use of mechanical ventilation can certainly cause complications for clients, one of which is Ventilator Associated Pneumonia (VAP). VAP is a lung infection caused by the use of a mechanical ventilator for more than 2 days. The prolonged duration of mechanical ventilator use is suspected to be one of the main factors leading to the occurrence of VAP. To determine the relationship between the duration of mechanical ventilator use and the incidence of Ventilator Associated Pneumonia (VAP) in the ICU of RSUD Karawang.The research method used is cross-sectional. The population used consists of patients who are on mechanical ventilation in the Intensive Care Unit (ICU) and have met the inclusion and exclusion criteria from January to November 2024, totaling 84 respondents. The sample size of 70 people was determined using the Slovin formula. The sampling method used is the consecutive sampling method. The statistical test method uses univariate analysis and bivariate analysis using the Chi-Square test. Out of 70 samples studied, there were 37 patients who were not affected by vap and 33 patients who were affected by vap. The correlation test yielded an Asymptotic Significance (2-sided) value of 0.045, thus the Asymptotic Significance (2-sided) value < α (0.05). There is a relationship between the duration of mechanical ventilator use and the incidence of Ventilator Associated Pneumonia (VAP) in the ICU of RSUD Karawang. Keywords: Ventilator, Ventilator Associated Pneumonia (VAP), ICU ABSTRAK Ventilator mekanik merupakan terapi invasive berupa penggunaan alat bantu yang bertugas mengambil alih fungsi pernapasan, nafas invasif. Selain digunakan sebagai alat bantu nafas, penggunaan ventilasi mekanik tentu saja dapat menimbulkan komplikasi pada klien salah satunya Ventilator Associated Pneumonia (VAP). VAP merupakan penyakit infeksi pada paru-paru yang disebabkan oleh penggunaan ventilator mekanik lebih dari 2 hari. Durasi lama penggunaan ventilator mekanik disinyalir menjadi salah satu faktor utama terjadiya VAP. Untuk mengetahui hubungan lama penggunaan ventilator mekanik dengan kejadian Ventilator Associated Pneumonia (VAP) di ruang ICU RSUD Karawang.Metode penelitian yang digunakan adalah cross sectional. Populasi yang digunakan adalah pasien yang menggunakan ventilator mekanik di Intensive Care Unit (ICU) yang sudah memenuhi kriteria inklusi dan eklusi dari bulan Januari-November tahun 2024 sebanyak 84 responden. Jumlah sampel sebanyak 70 orang ditentukan menggunakan formula Slovin. Metode sampling yang digunakan adalah metode consecutive sampling. Metode uji statistik menggunakan analisis uji univariat dan analisis bivariat menggunakan uji Chi-Square.Dari 70 sampel yang diteliti terdapat pasien yang tidak terkena vap sebanyak 37 orang dan yang terkena vap sebanyak 33 orang. Uji korelasi didapatkan hasil nilai Asymptotic Significance (2-sided) sebesar 0,045 sehingga nilai Asymptotic Significance (2-sided) < α (0,05).Terdapathubungan antara lama penggunaan ventilator mekanik dengan kejadian Ventilator Associated Pneumonia (VAP) di Ruang ICU RSUD Karawang. Kata Kunci: Ventilator, Ventilator Associated Peneumonia (VAP), ICU